Therapeutic Drug Monitoring by Dried Blood Spot: Progress to Date and Future Directions - Wilhelm, Abraham J.; den Burger, Jeroen C. G.; Swart, Eleonora L. (Clinical pharmacokinetics, 2014)
This article discusses dried blood spot (DBS) sampling in therapeutic drug monitoring (TDM). The most important advantages of DBS sampling in TDM are the minimally invasive procedure of a finger prick (home sampling), the small volume (children), and the stability of the analyte. Many assays in DBS have been reported in the literature over the previous 5 years. These assays and their analytical techniques are reviewed here. Factors that may influence the accuracy and reproducibility of DBS methods are also discussed. Important issues are the correlation with plasma/serum concentrations and the influence of hematocrit on spot size and recovery. The different substrate materials are considered. DBS sampling can be a valid alternative to conventional venous sampling. However, patient correlation studies are indispensable to prove this. Promising developments are dried plasma spots using membrane and hematocrit correction using the potassium concentration.